RELIGIOUS ARTIFACTS AS AGENTS: THE INTERSECTION BETWEEN AESTHETICS, SPIRITUALITY AND CULTURE - Lima, Maria Eduarda Campos; Oliveira, Ivana Araujo de Campos (Seven Editora, 2025)
The present study aims to analyze the intersection between art and religion from the anthropological perspective of Alfred Gell (1998), in "The Distributed Person", complemented by interviews with practitioners of different religious traditions. Religious artifacts are understood not merely as aesthetic objects but as active elements in the spiritual and social lives of individuals. This qualitative research is based on a literature review, incorporating, in addition to Gell (1998), the theoretical contributions of Latour (2008) and Vernant (1990, 1992). The empirical investigation revealed that both Catholics and followers of Afro-Brazilian religions attribute to religious images a mediating role between the human and the divine. In this context, works of art are endowed with a system of agency, capable of influencing and shaping individuals’ spiritual experiences. Thus, religious images are perceived as channels of communication and symbols that connect the sacred to everyday life, exerting a deep emotional, symbolic, and cultural impact.DOI: https://doi.org/10.56238/sevened2025.026-006